Fulfillment of the Constitutional Rights of Fisherwomen in Obtaining Fisheries and Marine Business Actor Cards - Sofiani, Trianah; Astuti, Fitria Widya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research discusses the fulfillment of the constitutional rights of female fishermen in obtaining a fisheries and maritime business card (KUSUKA). Despite Law Number 7 of 2016 regarding the Protection and Empowerment of Women, Fish Cultivators and Salt Farmers, there are still many female fishermen who have not yet made KUSUKA Cards and have the impact of note getting access to social services and safety guarantees when fishing for their rights. This research aims to analyze the reasons for not fulfilling the constitutional law rights of female fishermen. This research uses a qualitative approach with data obtained through interviews with village officials, female fishermen, and direct observation. The results of the research shows that the constitutional rights of female fishermen have not been fulfilled due to the lack of regulations that specifically regulate female fishermen to make it easier to obtain a KUSUKA Card. The legal consequences that fisherwomen get after the regulations regarding Fisheries and Maritime Business Actor Cards (KUSUKA) are issued are that fisherwoman are currently note guaranteed their right to receive risk insurance, social security or fishermen's insurance as well as assistance from the government because they don't yet have a KUSUKA Card as a fisherman's identity.